LGBT Portrayals in Advertising. Sexual conservatism and the effectiveness of ads depicting straight or trans characters. - Leonidou, Sophia; Voutsa, Maria C. (My University, 2023)
The depiction of transgender characters in advertising is essential for promoting acceptance of this community and reduce stereotyping behavior. Non-binary characters in advertising remain a controversial and understudied issue. Despite the growing evidence on the depiction of the sexes in advertising, there is limited reference to its effectiveness as well as the mediating effect of perceived irritation The present study focuses on to investigate the effectiveness of advertising depicting people from the LGBTQ+ community and identify the role of perceived irritation. Results revealed that sexually conservative (liberal) consumers indicate higher (lower) levels of perceived irritation which in turn lead to a less (more) positive Aad, Abr, and PI.
Keywords: LGBT; advertising effectiveness; sexual conservatism; irritation; transgender